Pleuropulmonary blastoma: A single-center case series of seven patients - M Masood Sidiqi; Ling Xu; Parshotam Gera; Colin Kikiros (Indian Journal of Child Health, 2021)
Introduction: Pleuropulmonary blastoma (PPB) is a rare and aggressive primary neoplasm of pleuropulmonary mesenchyme occurring in children. The International PPB Registry was established in 1988 to collect and assess data on PPB worldwide. Objectives: The objectives of the study were to assess the clinical characteristics, histopathology, genetic studies, management, and treatment outcomes of patients with PPB in our institution, and to compare with the published literature. Materials and Methods: We retrospectively reviewed the medical records of all PPB cases diagnosed at Princess Margaret Hospital for Children in West Australia over a period of 26 years (1990–2016). Their clinical characteristics, histopathology, genetic studies, management, and treatment outcomes were recorded. Results: Seven children (four boys and three girls) were treated for PPB at a mean age of 11.5 months (ranges 1 month–3.55 years). Histopathology showed type I PPB in five, type II in one, and type III in one. All seven patients underwent thoracotomy/lobectomy of the corresponding site. One patient required additional bladder resection for coexisting rhabdomyosarcoma. One patient was found to be positive for DICER1 gene mutation. Six patients received adjuvant chemotherapy with vincristine, Adriamycin, and cyclophosphamide regime, with the mean duration of treatment for five patients being 9.4 months excluding one patient who deceased without completion of chemotherapy. During a mean follow-up time of 9 years, the overall survival rate for this cohort was 85.7% (6/7). Conclusion: Our results are comparable to those reported in the literature. It is crucial for clinicians to consider PPB in the evaluation of patients presenting with a cystic lung abnormality, especially in cases with DICER1 mutation or a strong family history of unusual cancers